2019
DOI: 10.1007/s00277-019-03610-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between symptom burden and disability leave among patients with myeloproliferative neoplasms (MPNs): findings from the Living with MPN patient survey

Abstract: Patients with myeloproliferative neoplasms (MPNs) experience burdensome symptoms that negatively affect their quality of life. How MPN symptoms relate with medical disability leave (MDL) among patients with the disease has not been previously examined. Using data collected from the Living with MPNs patient survey, symptom burden and functional status were compared in patients who reported taking MDL due to their MPN versus patients who reported no changes in employment status. Among 592 patients who were emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The findings from the Landmark study are echoed in other surveys of PROs in MPN [6,[8][9][10]. In a study conducted in the UK and USA, significant reductions in QoL relative to controls were observed, as well as differences in QoL between UK and US patients, and in symptom burden between male and female patients [6].…”
Section: Impact Of Mpns On Patient-reported Outcomes (Pros)mentioning
confidence: 72%
See 3 more Smart Citations
“…The findings from the Landmark study are echoed in other surveys of PROs in MPN [6,[8][9][10]. In a study conducted in the UK and USA, significant reductions in QoL relative to controls were observed, as well as differences in QoL between UK and US patients, and in symptom burden between male and female patients [6].…”
Section: Impact Of Mpns On Patient-reported Outcomes (Pros)mentioning
confidence: 72%
“…The US ''Living with MPNs'' survey found that all three types of MPNs have a substantial negative impact on patients' employment status, career potential, and work productivity comparable to the impairment levels reported for other disabling chronic conditions [9,10]. While patients with MF and those with higher symptom burden reported the greatest impact, a notable proportion of patients with PV and ET and lower symptom burden were also severely impacted by their symptoms and corresponding impairments associated with their disease [9,10].…”
Section: Impact Of Mpns On Patient-reported Outcomes (Pros)mentioning
confidence: 90%
See 2 more Smart Citations
“…The Living with MPNs survey was a cross-sectional web-based questionnaire that has been previously described [ 13 , 15 ]. In brief, individuals 18 to 70 years of age with a diagnosis of MF, PV, or ET and living in the United States were eligible to participate.…”
Section: Methodsmentioning
confidence: 99%